Cultural validation of the Addenbrooke's Cognitive Examination Version III Urdu for the British Urdu-speaking population: a qualitative assessment using cognitive interviewing. Issue 12 (14th December 2018) - Mirza, Nadine; Panagioti, Maria; Waheed, Waquas
Abstract : Objectives: Our research determined whether the Addenbrooke's Cognitive Examination Version III (ACE-III) Urdu eliminated cultural bias through a qualitative assessment of its understanding and acceptability within the British Urdu-speaking population, employing cognitive interviews. Method: We aimed to recruit 25 participants fluent in speaking and writing Urdu, over the age of 60 years, able to give informed consent and who did not have a history of cognitive impairment. Participants were administered the ACE-III Urdu, and cognitive interviews were conducted, which involve obtaining verbal data on the individual's perception of the assessment overall, their understanding of the mental processes behind how they interpreted questions within the assessment and how they produced appropriate responses. This allows us to gauge the participants' overall thoughts on the Urdu ACE-III before applying question-formatted prompts to every ACE-III Urdu item. Results: We recruited 25 participants, 12 women (48%), ranging from ages 60 years to 85 years (M=69.12, SD=6.57), all from Greater Manchester. Participants came from varied socioeconomic backgrounds, with 22 identifying as Pakistani, one as British Pakistani and two as East African. Across 19 ACE-III Urdu items, 7 required changes based on participant feedback: item 5a: fluency; items 6, 18 and 19: memory; items 12 and 13: language; and item 17: visuospatial abilities. The need for some of these changes was realised after 21 participants, due to persistently reoccurring issues, and these were applied before the last four participants. Overall, the ACE-III Urdu was considered easy and straightforward by all 25 participants, who understood items and felt the ACE-III Urdu was appropriate, not just for them, but for British Urdu speakers in general. Conclusion: Our cognitive interviews determined the ACE-III Urdu was acceptable, especially with regards to cultural context, but further changes were made to ensure understanding. Therefore, we adapted the ACE-III Urdu in accordance with feedback, resulting in our finalised version being culturally validated.